Use of in vitro assays to assess the potential cytotoxic, genotoxic and antigenotoxic effects of vanillic and cinnamic acid - Taner, Gökçe; Vardar, Deniz Ozkan; Aydin, Sevtap; Aytac, Zeki; Basaran, Ahmet; Basaran, Nursen (Taylor & Francis Ltd, 2017)
Vanillic acid (VA) found in vanilla and cinnamic acid (CA) the precursor of flavonoids and found in cinnamon oil, are natural plant phenolic acids which are secondary aromatic plant products suggested to possess many physiological and pharmacological functions. In vitro and in vivo experiments have shown that phenolic acids exhibit powerful effects on biological responses by scavenging free radicals and eliciting antioxidant capacity. In the present study, we investigated the antioxidant capacity of VA and CA by the trolox equivalent antioxidant capacity (TEAC) assay, cytotoxicity by neutral red uptake (NRU) assay in Chinese Hamster Ovary (CHO) cells and also the genotoxic and antigenotoxic effects of these phenolic acids using the cytokinesis-blocked micronucleus (CBMN) and the alkaline comet assays in human peripheral blood lymphocytes. At all tested concentrations, VA (0.17-67.2 mu g/ml) showed antioxidant activity but CA (0.15-59.2 mu g/ml) did not show antioxidant activity against 2,2-azino-bis (3-ethylbenz-thiazoline-6-sulphonic acid) (ABTS). VA (0.84, 4.2, 8.4, 16.8, 84 and 168 mu g/ml) and CA (0.74, 3.7, 7.4, 14.8, 74, 148 mu g/ml) did not have cytotoxic and genotoxic effects alone at the studied concentrations as compared with the controls. Both VA and CA seem to decrease DNA damage induced by H2O2 in human lymphocytes.
Keywords: Vanillic acid; cinnamic acid; trolox equivalent antioxidant capacity; neutral red uptake assay; cytokinesis-block micronucleus assay; comet assay; CHO cells; human lymphocytes